The Law on transfer and business taxation : with illustrations, problems, and solutions - De Leon, Hector S. (Manila, Philippines : Rex Book Store, 2000)
Intended primarily as a textbook in colleges and universities, it has been designed likewise to serve as useful reference or guide not only to tax officials and practitioners but also to the young businessmen and the ordinary tax payers who have no previous background on the subject.
Introduction -- Part I. Transfer taxation -- Chapter 1. Estate tax -- A. Preliminary topics -- B. Gross estate -- C. Exclusions and exemptions -- D. Deductions -- E. Valuation -- F. Schedule and computation of the tax -- G. Basic concepts of succession -- H. Notice of death and filing of return -- I. Payment and sactions -- Chapter 2. Donor's tax -- A. Preliminary topics -- B. Application of the tax -- C. Exemptions or deductions -- D. Valuation -- E. Schedule and computation of the tax -- F. Return, payment, and sanctions -- Part II. Business taxation -- Chapter 1. In general -- Chapter 2. Value-added tax -- A. Preliminary topics -- B. Imposition of the tax -- C. Computation of the tax -- D. Compliance requirements -- Chapter 3. Other percentage taxes -- A. Preliminary topics -- B. Tax on small business enterprises -- C. Tax on carrier and keepers of garages -- D. Tax on franchises -- E. Overseas communications tax -- F. Tax on banks, financial intermediaries, and finance companies -- G. Tax on life insurance companies and agents of foreign insurance companies -- H. Amusement taxes -- I. Tax on sale, barter or exchange of shares of stocks -- J. Returns and payment of percentage taxes -- Chapter 4. Excise taxes on certain goods -- A. Preliminary topics -- B. Goods subject to excise taxes -- C. Accrual and payment of excise taxes -- D. Tax on alcohol products -- E. Tax on tobacco products -- F. Tax on petroleum products -- G. Excise tax on miscellaneous articles -- H. Tax on mineral products -- I. Administrative provisions -- J. Penal Provisions -- Chapter 5. Documentary stamp taxes -- A. Preliminary topics -- B. Payment of the taxes and sanctions -- C. Rates and bases of the taxes -- Chapter 6. Statutory offenses and penalties -- A. Additions to the tax -- B. Crimes, other offenses, and forfeitures -- Chapter 7. Compliance requirements -- A. Bookkeeping regulations -- B. Audit by independent certified public accountants -- C. Inspection and examination -- D. Bookkeping forms -- E. Administrative provisions -- F. Registration of taxpayers -- Chapter 8. Local taxation -- A. Introduction -- B. Local taxing power in general -- C. Taxing and other revenue-raising powers of provinces -- D. Taxing and other revenue-raising powers of municipalities -- E. Taxing and other revenue-raising powers of cities -- F. Taxing and other revenue-raising powers of barangays -- G. Common revenue-raising powers -- H. Community tax -- I. Tax ordinance -- J. Collection of taxes -- K. Civil remedies for collection of revenues -- L. Tax payer's remedies -- M. Real property taxes -- 1. Introduction -- 2. Appraisal and assessment of real property -- 3. Appeal on assessment -- 4. Imposition of the tax -- 5. Special levies on real property -- 6. Collection of the tax -- 7. Disposition of proceeds -- 8. Special provisions.
Keywords: BUSINESS TAX -- LAW -- PHILIPPINES